Answer:
1. Distributive property.
2. Combining like terms.
3. Addition property of equality.
4. Division property of equality.
Step-by-step explanation:
- The Distributive property states that:
![a(b+c)=ab+ac\\\\a(b-c)=ab-ab](https://tex.z-dn.net/?f=a%28b%2Bc%29%3Dab%2Bac%5C%5C%5C%5Ca%28b-c%29%3Dab-ab)
- The Addition property of equality states that:
![If\ a=b\ then\ a+c=b+c](https://tex.z-dn.net/?f=If%5C%20a%3Db%5C%20then%5C%20a%2Bc%3Db%2Bc)
- The Subtraction property of equality states that:
![If\ a=b\ then\ a-c=b-c](https://tex.z-dn.net/?f=If%5C%20a%3Db%5C%20then%5C%20a-c%3Db-c)
- The Multiplication property of equality states that:
![If\ a=b\ then\ a*c=b*c](https://tex.z-dn.net/?f=If%5C%20a%3Db%5C%20then%5C%20a%2Ac%3Db%2Ac)
- The Division property of equality states that:
![If\ a=b\ then\ \frac{a}{c}=\frac{b}{c}](https://tex.z-dn.net/?f=If%5C%20a%3Db%5C%20then%5C%20%5Cfrac%7Ba%7D%7Bc%7D%3D%5Cfrac%7Bb%7D%7Bc%7D)
Given the following equation:
![4(3x-8)-4=24](https://tex.z-dn.net/?f=4%283x-8%29-4%3D24)
We can identify that the methods Maria used to solve it and the order, are:
1. Distributive property:
![(4)(3x)-(4)(8)-4=24\\\\12x-32-4=24](https://tex.z-dn.net/?f=%284%29%283x%29-%284%29%288%29-4%3D24%5C%5C%5C%5C12x-32-4%3D24)
2. Combining (or adding) like terms:
![12x-36=24](https://tex.z-dn.net/?f=12x-36%3D24)
3. Addition property of equality, because she added 36 to both sides of the equation:
![12x-36+36=24+36\\\\12x=60](https://tex.z-dn.net/?f=12x-36%2B36%3D24%2B36%5C%5C%5C%5C12x%3D60)
4. Division property of equality, because she divided both sides of the equation by 12:
![\frac{12x}{12}=\frac{60}{12}\\\\x=5](https://tex.z-dn.net/?f=%5Cfrac%7B12x%7D%7B12%7D%3D%5Cfrac%7B60%7D%7B12%7D%5C%5C%5C%5Cx%3D5)
Answer: i'm pretty sure the answer is 10.5
Step-by-step explanation: <em>i multiplied 5/7 by 14.7 </em>
I'm sorry if this is wrong but if it's right i need brainliest to rank up so please mark me brainliest:)
Answers: ![x](https://tex.z-dn.net/?f=x%3C-8)
1. Switch sides
![-9x+8>80](https://tex.z-dn.net/?f=-9x%2B8%3E80)
2. Subtract by 8 from both sides of equation.
![-9x+8-8>80-8](https://tex.z-dn.net/?f=-9x%2B8-8%3E80-8)
3. Simplify.
![-9x>72](https://tex.z-dn.net/?f=-9x%3E72)
4. Multiply by -1 from both sides of equation. (it's should be the reverse inequality).
![(-9x)(-1)](https://tex.z-dn.net/?f=%28-9x%29%28-1%29%3C72%28-1%29)
5. Simplify.
![9x](https://tex.z-dn.net/?f=9x%3C-72)
6. Then you had to divide by 9 from both sides of equation.
![\frac{9x}{9}< \frac{-72}{9}](https://tex.z-dn.net/?f=%5Cfrac%7B9x%7D%7B9%7D%3C%20%5Cfrac%7B-72%7D%7B9%7D)
7. Simplify.
![\frac{9x}{9}=x](https://tex.z-dn.net/?f=%5Cfrac%7B9x%7D%7B9%7D%3Dx)
8. Divide by the numbers.
![\frac{9}{9}=1](https://tex.z-dn.net/?f=%5Cfrac%7B9%7D%7B9%7D%3D1)
![=x](https://tex.z-dn.net/?f=%3Dx)
![\frac{-72}{9}=-8](https://tex.z-dn.net/?f=%5Cfrac%7B-72%7D%7B9%7D%3D-8)
9. Divide by the numbers.
![\frac{72}{9}=8](https://tex.z-dn.net/?f=%5Cfrac%7B72%7D%7B9%7D%3D8)
![=-8](https://tex.z-dn.net/?f=%3D-8)
![x](https://tex.z-dn.net/?f=x%3C-8)
____________________________________________________________
Hope this helps!
Thank you for posting your question at here on brainly.
Have a great day!
________________________________________________________
Answer:
8x - 14 = 5x + 34 (alternate exterior angles)
8x - 5x = 34 + 14
3x = 48
x = 48/3
x = 16
5y + 16 + 8x - 14 = 180 (linear pair)
5y + 16 + 8(16) - 14 = 180
5y + 16 + 128 - 14 = 180
5y + 130 = 180
5y = 180 - 130
5y = 50
y = 50/5
y = 10
∠ (8x - 14) = 114 [(8 × 16 -14)=114]
∠ (5x + 34) = 114 [(5 × 16 +34)=114]
∠ (5y + 16) = 66 [(5 × 10 +16)=66]
hope this helps you!
Assuming these are 4^(1/7), 4^(7/2), 7^(1/4) and 7^(1/2), the conversion process is pretty quick. the denominator, or bottom, of your fraction exponent becomes the "index" of your radical -- in ∛, "3" is your index, just for reference. the numerator, aka the top of the fraction exponent, becomes a power inside the radical.
4^(1/7) would become ⁷√4 .... the bottom of the fraction becomes the small number included in the radical and the 4 goes beneath the radical
in cases such as this one, where 1 is on top of the fraction radical, that number does technically go with the 4 beneath the radical--however, 4¹ = 4 itself, so there is no need to write the implied exponent.
4^(7/2) would become √(4⁷) ... the 7th power goes with the number under your radical and the "2" becomes a square root
7^(1/4) would become ⁴√7 ... like the first answer, the bottom of the fraction exponent becomes the index of the radical and 7 goes beneath the radical. again, the 1 exponent goes with the 7 beneath the radical, but 7¹ = 7
7^(1/2) would become, simply, √7